CLARE ON THE WANE. (9th December 2015) - Hodgson, Andrew
Abstract: This essay considers John Clare's success as a writer of poems about imaginative failure. It takes as its points of focus three poems composed in 1832, the year of Clare's move from his home village of Helpston to nearby Northborough: 'Decay A Ballad', 'Remembrances', and 'The Flitting'. Though the poems have often been praised, little attention has been paid to the question of their style. Clare's achievement in these poems, the essay suggests, has to do with his deployment of an idiom which, in its irregularities and apparent waywardness, proves curiously appropriate to the poems' dealings with the loss of poetic powers. In so doing, the essay charts Clare's contribution to a common post-Romantic poetic genre and opens up a new perspective on the originality of his voice more widely.